2015
DOI: 10.5847/wjem.j.1920-8642.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Performance of cardiopulmonary resuscitation during prolonged basic life support in military medical university students: A manikin study

Abstract: CPR was found to be related to gender, body weight, and body mass index of students in this study. The quality of chest compressions was well maintained in male students during 8 minutes of conventional CPR but declined rapidly in female students after 2 minutes according to the latest national guidelines. Physical fitness and rescuer fatigue did not affect the quality of ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
0
16
2
Order By: Relevance
“…[15] Though we found that as our subjects' age increased, those who were >62 years compressed at a significantly shallower depth, we did see a trend towards shallower depth when the age of our subjects was >52 years. A study by Papalexopoulou et al [6] reported that the retention of CPR skills decreases over time and similarly hypothesized that it may be due to the weakening of physical stamina with increasing age.…”
Section: Discussioncontrasting
confidence: 50%
“…[15] Though we found that as our subjects' age increased, those who were >62 years compressed at a significantly shallower depth, we did see a trend towards shallower depth when the age of our subjects was >52 years. A study by Papalexopoulou et al [6] reported that the retention of CPR skills decreases over time and similarly hypothesized that it may be due to the weakening of physical stamina with increasing age.…”
Section: Discussioncontrasting
confidence: 50%
“…Also the SAVE-J study revealed an improved neurological outcome in patients with OHCA with shockable rhythm treated by a treatment bundle including ECPR, therapeutic hypothermia and intra-aortic balloon pump. [17] Further large studies implementing such strategies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…ECPR was introduced in the 1960s to improve neurological outcomes. [17] Recently, observational studies have reported an association between ECPR and improved survival. The present study provides a current review of survival to discharge and long-term neurological outcome for CA patients who have received ECPR compared with CCPR.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the inclusion of CPR early in medical curricula is thought to increase medical students' awareness and appreciation of this vital skill [2]. Despite being wellestablished and one of the most effective resuscitative measures for patients in cardiac arrest, lack of knowledge, insufficient training, and inadequate practice of CPR have been documented among medical students and junior doctors in high-income as well as low-and middle-income countries (LMICs) [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%